Transcriptional Reprogramming and Novel Therapeutic Approaches for Targeting Prostate Cancer Stem Cells - Civenni, Gianluca; Albino, Domenico; Shinde, Dheeraj; Vázquez, Ramiro; Merulla, Jessica; Kokanovic, Aleksandra; Mapelli, Sarah N.; Carbone, Giuseppina M.; Catapano, Carlo V. (Frontiers in Oncology, 2019)
Prostate cancer is the most common malignancy in men and the second cause of cancer-related deaths in western countries. Despite the progress in the treatment of localized prostate cancer, there is still lack of effective therapies for the advanced forms of the disease. Most patients with advanced prostate cancer become resistant to androgen deprivation therapy (ADT), which remains the main therapeutic option in this setting, and progress to lethal metastatic castration-resistant prostate cancer (mCRPC). Current therapies for prostate cancer preferentially target proliferating, partially differentiated and AR-dependent cancer cells that constitute the bulk of the tumor mass. However, the subpopulation of tumor-initiating or tumor-propagating stem-like cancer cells is virtually resistant to the standard treatments causing tumor relapse at the primary or metastatic sites. Understanding the pathways controlling the establishment, expansion and maintenance of the cancer stem cell (CSC) subpopulation is an important step toward the development of more effective treatment for prostate cancer, which might enable ablation or exhaustion of CSCs and prevent treatment resistance and disease recurrence. In this review, we focus on the impact of transcriptional regulators on phenotypic reprogramming of prostate CSCs and provide examples supporting the possibility of inhibiting maintenance and expansion of the CSC pool in human prostate cancer along with the currently available methodological approaches. Transcription factors are key elements for instructing specific transcriptional programs and inducing CSC-associated phenotypic changes implicated in disease progression and treatment resistance. Recent studies have shown that interfering with these processes causes exhaustion of CSCs with loss of self-renewal and tumorigenic capability in prostate cancer models. Targeting key transcriptional regulators in prostate CSCs is a valid therapeutic strategy waiting to be tested in clinical trials.